Malnutrition and climate patterns in the ASALs of Kenya: A resilience analysis based on a pseudo-panel dataset - Signorelli, Sara; Azzarri, Carlo; Roberts, Cleophelia (International Livestock Research Institute, 2016)
This study showed how arid and semi-arid areas of Kenya are particularly affected by undernutrition in women and children. Despite undernutrition improving in the rest of the country, in the ASAL areas the trends appear to be negative, particularly with respect to wasting in children and women being underweight. Temperature shocks emerge as the most detrimental factor for nutrition, again especially in ASAL areas. Droughts, on the other hand, seem to play a significant role only in affecting stunting, while NDVI plays a mixed role, with some cases where more vegetation is associated with higher levels of undernutrition. Overall, the availability of a non-agricultural job within the household is positively associated with nutritional outcomes, as is women’s education, especially in ASAL counties. However, they are also associated with bigger losses in the event of temperature shocks, which raises a query on the role of non–agricultural activities in increasing resilience. Results show that expected climate change bears the potential to greatly harm the Kenyan population living in ASAL areas, and that what is currently believed to be viable solutions to increase resilience may not deliver the results promised. More investigation and research is needed to identify programming strategies to implement, which will enable populations to better cope with climate change and the associated challenges ahead.